I look, therefore I see. Using action observation in improving strength and conditioning techniques - Sakadjian, A.; Panchuk, D.; Pearce, A. J. (Strength and Conditioning Journal, 2013)
Action observation (ao) is learning a skill through observing another individual (model) performing the same skill. Ao is the most commonly used method of instruction for skill acquisition. In athlete preparation, coaching technical and novel resistance training (rt) exercises to athletes is common, but at times, avoided because of time efficiency and safety concerns. This article discusses current evidence surrounding the application of ao in coaching during skill acquisition and the limited but growing evidence illustrating the potential of implementing ao in an rt setting.